Forging Communities in Colonial Alta California - Douglass, John G.; Hull, Kathleen L. (Archaeology of indigenous-colonial interactions in the Americas., 2018)
Between 1769 and 1834, an influx of Spanish, Russian, and then American colonists streamed into Alta California seeking new opportunities. Their arrival brought the imposition of foreign beliefs, practices, and constraints on Indigenous peoples. Forging Communities in Colonial Alta California reorients understandings of this dynamic period, which challenged both Native and non-Native people to reimagine communities not only in different places and spaces but also in novel forms and practices. The contributors draw on archaeological and historical archival sources to analyze the generative processes and nature of communities of belonging in the face of rapid demographic change and perceived or enforced difference. Contributors provide important historical background on the effects that colonialism, missions, and lives lived beyond mission walls had on Indigenous settlement, marriage patterns, trade, and interactions. They also show the agency with which Indigenous peoples make their own decisions as they construct and reconstruct their communities. With nine different case studies and an insightful epilogue, this book offers analyses that can be applied broadly across the Americas, deepening our understanding of colonialism and community.